2013
DOI: 10.1002/macp.201300581
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of RAFT on the Microstructure and the Mechanical Properties of Photopolymerized Poly(butyl acrylate) Networks

Abstract: Statistical networks of butyl acrylate and 1,4‐butanediol diacrylate are photopolymerized in bulk, both in the presence and absence of the RAFT agent EPHT. The amounts of crosslinker and RAFT agent are varied. The Young's moduli of the RAFT networks are always lower than those of conventionally obtained networks. With increasing amounts of RAFT agent, the Young's modulus decreases and the strain at break values increase, respectively. The network density, the apparent molar mass of the network chains and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 29 publications
8
45
0
Order By: Relevance
“…The samples obtained via conventional free radical polymerization (RAFT concentration zero) show the highest moduli. These findings are in agreement with several previous studies which also revealed lower moduli for gels obtained by controlled radical polymerization [11,12,15].…”
Section: Influence Of the Amount Of Cross-linker And Raft Agentsupporting
confidence: 95%
See 4 more Smart Citations
“…The samples obtained via conventional free radical polymerization (RAFT concentration zero) show the highest moduli. These findings are in agreement with several previous studies which also revealed lower moduli for gels obtained by controlled radical polymerization [11,12,15].…”
Section: Influence Of the Amount Of Cross-linker And Raft Agentsupporting
confidence: 95%
“…The data seem to follow a single curve irrespective of how the synthesis was performed, with some scatter presumably due to experimental uncertainty. Similar results regarding the swelling properties of RAFT polymerized networks have been obtained before by Crescenzi et al [11], Henkel and Vana [12] and Lu et al [17].…”
Section: Influence Of the Amount Of Cross-linker And Raft Agentsupporting
confidence: 86%
See 3 more Smart Citations